Etiopathogenetic factors, thyroid functions and thyroid autoimmunity in melasma patients - Çakmak, Seray Külcü; Özcan, Nimet; Kılıç, Arzu; Koparal, Suha; Artüz, Ferda; Çakmak, Atıl; Köse, Kenan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Melasma is a common chronic, acquired pigmentation disorder with a significant impact on the quality of life of patients. Aim: To investigate the etiopathogenetic factors, thyroid functions and thyroid autoimmunity in patients with melasma. Material and methods : Forty-five women with melasma and 45 age-matched healthy women were included in the study group. A detailed history was taken from the patients including triggering factors of melasma. Serum free triiodothyronine (FT3), free thyroxine (FT4), thyroid-stimulating hormone (TSH), anti-thyroglobulin (AbTG) and anti-thyroid peroxidase (Ab-TPO) were measured and thyroid ultrasonography was performed for each subject. Results : In 26.7% of patients, pregnancy, in 17.8%, oral contraceptive use and in 13.3%, intense sunlight exposure were the triggering factors. 17.8% of patients had a family history of melasma. FT4, TSH and AbTG levels were significantly higher in the patient group. Conclusions : The results suggest that a combination of factors including pregnancy, oral contraceptive use, sunlight and genetic factors often trigger melasma. Thyroid hormones and thyroid autoimmunity may also play a role in the pathogenesis which needs to be proven by further studies.